Physiotherapy outcome measures of haemophilia acute bleed episodes: What matters to patients?. Issue 6 (15th September 2019) - Bradshaw, Elizabeth; McClellan, Carey; Whybrow, Paul; Cramp, Fiona
Abstract: Introduction: The research was conducted at a UK teaching hospital and Haemophilia Comprehensive Care Centre (CCC) as part of a research programme investigating physiotherapy for acute bleed management. Aim: The aim of the study was to understand the perspectives of people with haemophilia (PWH) on validated outcome measures (OM) and whether these measures capture changes relevant to them whilst recovering from an acute bleed episode. Methods: Any person with haemophilia registered to the CCC who reported an acute bleed within the past 2 years was invited to participate. Semi‐structured interviews or workshops (activity‐focused discussions with small groups) were conducted with PWH who had received physiotherapy treatment in the previous two years. These were used to explore opinions of PWH of commonly used outcome measures. Results: Eight male PWH participated, mean age 61 years, ranging between 39 and 71. Seven participants had severe haemophilia A and 1 had von Willebrands. Participants described numerical rating scales of pain as abstract and expressed a preference for verbal or visual descriptors. In relation to function, the men generally found haemophilia‐specific OM to be more relevant. The EuroQol 5‐Dimension 5‐Level (EQ5D‐5L) and Haemophilia and Exercise Project Test Questionnaire (HEP‐Test‐ Q ) were considered as good measures due to brevity and ability to capture relevant changes promptly. Conclusion: Participants in this study reported a preference for short OMs that allow them to reference their ability during the acute bleed episode in comparison with their normal function.